ACARORUM CATALOGUS VI. Order Mesostigmata. Gamasina: Dermanyssoidea (Rhinonyssidae, Spinturnicidae) - Petar Beron (Advanced Books, 2020)
This volume contains data on two families, 16 genera and 445 species of the families Rhinonyssidae (parasites in the respiratory system of birds) and 12 genera and 110 species of Spinturnicidae (ectoparasites of bats).